Respuesta :
Answer:
6y^2 − 11y − 35
Step-by-step explanation:
(2y + −7)(3y + 5)
=(2y)(3y)+(2y)(5)+(−7)(3y)+(−7)(5)
=6y2+10y−21y−35
=6y2−11y−35
The product of two given polynomial is (6y² - 11y -35).
What is a polynomial?
"A polynomial is an expression consisting of indeterminates and coefficients, that involves only the operations of addition, subtraction, multiplication, and non-negative integer exponentiation of variables."
Therefore, the product is
= (2y - 7)(3y + 5)
= (6y² - 21y + 10y -35)
= (6y² - 11y -35)
Learn more about a polynomial here: https://brainly.com/question/11298739
#SPJ3